The Quiet Hours : City Photographs - Melman, Mike (Book collections on Project MUSE., 2003)
With an Essay by Bill HolmIn The Quiet Hours, Mike Melman records a vanishing era of Minnesotas towns and cities through a series of seventy black-and-white photographs taken from 1985 to 2002. Working in the half-light of predawn hours, Melman brings a new perspective to familiar places. In his essay, Bill Holm compares Melmans work to that of Walt Whitman and Carl Sandburg, artists who embrace and celebrate the urban experience.